Eficácia horizontal dos direitos fundamentais nos contratos de franquia - Testa, Gustavo Nori (2012)
The recognition of the impact of values and principles laid down by the Constitution of 1988 with the Civil protests not as a mere trend toward satisfaction method only, but as a real movement endowed with a concern focused on building a legal system that is while sensitive to the problems and challenges pertaining to contemporary society and enable a full economic development, a factor driving the commercial contractual relationships such as franchising, for example. Among these "new" challenges contractual theory will have to face considering the new reality, this paper will pursue the goal of a contractual right aligned to these new constitutional statements, particularly those connected to fundamental rights, evaluating possible impacts on human dignity, and further unfolding consequences upon the Constitutional and Contractual Law